Carbon, texture, pH, bulk density in sandy soils of Senegalese groundnut basin (2016-2018) - Malou, Oscar Pascal; Moulin, Patricia; Chevallier, Tiphaine; Masse, Dominique; Vayssières, Jonathan; Badiane-Ndour, Ndèye Yacine; Tall, Laure; Thiam, Abou; Chapuis-Lardy, Lydie (DataSuds, 2021)
Dataset used for a paper published in Regional Environmental Change (2021) "Estimates of carbon stocks in sandy soils cultivated under local management practices in Senegal’s groundnut basin". Data comprised Sheet 1: Measured data (total carbon content, pH in water, pH in 1M KCl, 5 textural fractions for soil samples collected at 0-10 cm and 10-30 cm depth) with approximate UTM coordinates of fields and internal sample number (n=439). Sheet 2: visNIRS-based predicted data for soil carbon content and textural fractions with approximate UTM coordinates of plots, village names and internal sample number (n=3197). Sheet 3: measured (n=386) and estimated (n = 3240) bulk density of soil (0-10 and 10-30 cm layers). Sheet 4: Calculated carbon stocks in the topsoil (0-30 cm; n=1813 plots) with approximate UTM coordinates, information on type of fields and soils (Senegalese soil classification).